THE NEW FACE OF BOARDING SCHOOL EDUCATION - Supriyadi, Agus; Sholeha, Maratus (INCARE, International Journal of Educational Resources, 2023)
As Islamic educational institutions, pesantren are still claimed to be underdeveloped educational institutions, often even "crowned" only for the benefit of those who are unable or poor, producing people who are exclusive, fanatical, and even at a very sad behavior, namely "terrorism." considered to originate from Islamic educational institutions, because in fact several Islamic educational institutions were "considered" as the origin of the group. Even though this "assumption" is wrong and can be rejected, because there are no Islamic educational institutions that aim to produce or print groups of people like that. Based on the results of the study, it was found that there are three faces of education in Islamic boarding schools. First, Islamic boarding schools that organize formal education through Islamic boarding schools, such as elementary, junior high, high school/vocational school, and PTU. Second, Islamic boarding schools that organize formal education through Islamic boarding schools such as MI, MTs, MA/MAK, and PTAI. Third, Islamic boarding schools that organize formal education in the SPM/PDF and Ma'had Aly pathways. In addition, Islamic boarding schools also organize non-formal and informal education. The accusation that religious education in Islamic boarding schools is experiencing setbacks and is not in accordance with the times is also not true because Islamic boarding schools have the principle of al-muhafadhotu 'ala qodimis sholih wal akhdzu biljadidil ashlah, namely maintaining the old which is good and taking the new which is better.